2012
DOI: 10.1586/erv.12.39
|View full text |Cite
|
Sign up to set email alerts
|

Cancer vaccines: should we be targeting patients with less aggressive disease?

Abstract: There is enthusiasm for using vaccines to stimulate the immune system to treat cancer. In this article, the authors review the evolution of vaccines evaluated in clinical trials, starting with Phase III trials in metastatic disease and progressing to trials in the adjuvant setting. Data from these trials suggest that cancer vaccines may be more effective in patients with lower volume disease, and data from the E75 peptide vaccine trials suggest that vaccines may be most effective in less aggressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…In contrast, only a minority of patients currently benefit from cancer therapeutic vaccination, although for some patients the benefit can be substantial [1,7]. The challenges in developing highly effective therapeutic cancer vaccines, compared to prophylactic vaccines, Accordingly, clinical evidence indeed shows that patients with less advanced disease are more likely to benefit from active immunotherapy [8][9][10].…”
Section: Therapeutic Cancer Vaccinesmentioning
confidence: 99%
“…In contrast, only a minority of patients currently benefit from cancer therapeutic vaccination, although for some patients the benefit can be substantial [1,7]. The challenges in developing highly effective therapeutic cancer vaccines, compared to prophylactic vaccines, Accordingly, clinical evidence indeed shows that patients with less advanced disease are more likely to benefit from active immunotherapy [8][9][10].…”
Section: Therapeutic Cancer Vaccinesmentioning
confidence: 99%
“…7 This is one reason that many studies have suggested that immunotherapy should ideally be used earlier in the disease course in patients with lower tumor burdens. 8,9 Other studies have suggested combining vaccine with standard therapies in a manner designed to minimize or neutralize the immunosuppressive factors elaborated by or harbored within the tumor. [10][11][12] (The myriad important features of the tumor microenvironment, and their negative impact on the function of antitumor T cells, is beyond the scope of this brief commentary.…”
Section: Understanding the "New Kid"mentioning
confidence: 99%
“…One possible explanation for this failure is attributed to the fact that early trials mostly included late-stage patients, generally displaying severe systemic immune suppression that in the ‘pre-immune checkpoint inhibitor’ era of immunotherapy could hardly be overcome. 39 Then small clinical pilot studies (phase I/II) were launched exploring vaccination with mutated Kras and p53 peptides for their clinical benefit. 40,41 Vaccination trials with mutated Kras peptides in advanced-stage pancreatic cancer patients resulted in longer survival of immune responders compared to non-responding patients.…”
Section: Introductionmentioning
confidence: 99%